ANALISIS KANDUNGAN KARAGINAN DAN KELAYAKAN USAHA AGROINDUSTRI RUMPUT LAUT DI KABUPATEN MOROWALI - Sulistiawati, Dwi; ya'la, Zakirah Raihani; Rosyida, Eka (FAPETKAN UNTAD, 2011)
The site observational is at Morowali Regency, sample take is done on south Bungku district with 5 villages, which are Waru Waru, Jawi Jawi, Kaleroang, Bunginkela and Buajangka. Executed research up to 8 months. Observational target using survey method with direct sampling at the site as simple randoms sampling and purposives sampling, and direct interview with quesioner's. Output that resulting which is carrageenan analysis and seaweed agribusiness effort feasibility study. The product of carrageenan extraction result the higher purification points out that 30% available on Jawi Jawi’s seaweed, the lower (26,45 %) found on Waru Waru, and Morowali regency equals as big as 28.36%. Results of seaweed agribusiness effort feasibility study using five investment criterion showed that carrageenan agroindustri's effort is feasible.Key words : Agroindustry, carrageenan, seaweeds.